Effects of Brand Origin and Country-of-Origin from the Perspectives of Manufacturers and Consumers - Chiam, Daphne Mei-Ling (2003)
Brand origin (BO) relates to the place where a product or brand was first created or produced. On the other hand, the location where the product is made is known as the country-of-origin (COO). While past researches have provided contradicting conclusions on the importance of BO and COO, this paper has proven that both BO and COO are important to the consumers in their shopping and purchasing decisions. This is further evident when consumers confirm that they are willing to pay a premium for a preferred BO or COO. However, the results are different for the four product categories tested. Another interesting aspect of this paper is how BO is perceived to be less important than COO when past researches have indicated the reverse. The paper also measured consumers’ preference for “Western” and Asian brands, with the former being preferred. In view that Japan is a developed country with high quality standards and technological advancements, equivalent to the Westerners; Japan is classified as a “Western” brand for the purpose of this study. Consumers were also asked for their preference in relation to products made in developed and developing countries, where they expressed preference for the former. To complete the research, these issues were also tested with manufacturers and interestingly, results showed that manufacturers’ views were contradictory to consumers’ beliefs. The conflicting results between product categories; past and present studies; as well as manufacturers and consumers bring light to 3 issues: 1. Products which a consumer takes time in seeking information and understanding are less sensitive to BO and COO effects since increased familiarity of the product decreases the consumers’ sensitivity towards these effects; 2. BO is perceived as less important than COO when consumers do not see a difference between BO and COO or when they do not have a choice to purchase a preferred origin; and 3. The lack of understanding by manufacturers of the Malaysian consumer could be due to locally-based manufacturers using business models which are wholly imported from their foreign headquarters.